2017
DOI: 10.1016/s0140-6736(17)30317-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of complicated disease course for children newly diagnosed with Crohn's disease: a multicentre inception cohort study

Abstract: Summary Background Stricturing and penetrating complications account for substantial morbidity and health-care costs in paediatric and adult onset Crohn’s disease. Validated models to predict risk for complications are not available, and the effect of treatment on risk is unknown. Methods We did a prospective inception cohort study of paediatric patients with newly diagnosed Crohn’s disease at 28 sites in the USA and Canada. Genotypes, antimicrobial serologies, ileal gene expression, and ileal, rectal, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
430
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 517 publications
(457 citation statements)
references
References 31 publications
(37 reference statements)
22
430
1
4
Order By: Relevance
“…We were specifically interested to know whether gene programs expressed in circulating neutrophils would reflect those that we recently reported in the gut. 12 The gene expression results with GMSI-Lo neutrophils were remarkably similar to those obtained in pretreatment ileal biopsies for CD patients who went on to develop strictures. 12 This included upregulation of an extracellular matrix production gene signature and suppression of a mitochondrial respiration gene signature in GMSI-Lo neutrophils relative to control neutrophils.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…We were specifically interested to know whether gene programs expressed in circulating neutrophils would reflect those that we recently reported in the gut. 12 The gene expression results with GMSI-Lo neutrophils were remarkably similar to those obtained in pretreatment ileal biopsies for CD patients who went on to develop strictures. 12 This included upregulation of an extracellular matrix production gene signature and suppression of a mitochondrial respiration gene signature in GMSI-Lo neutrophils relative to control neutrophils.…”
Section: Discussionsupporting
confidence: 58%
“…12 The gene expression results with GMSI-Lo neutrophils were remarkably similar to those obtained in pretreatment ileal biopsies for CD patients who went on to develop strictures. 12 This included upregulation of an extracellular matrix production gene signature and suppression of a mitochondrial respiration gene signature in GMSI-Lo neutrophils relative to control neutrophils. These data suggest an important role for GM-CSF in regulating these critical gene programs linked to patient outcomes, which will now be tested in purified ileal epithelial, myeloid, and myofibroblast cells.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Given the limitations of this study (retrospective subgroup analysis, underpowered sample size), the authors concluded that the main explanation for the lack of benefit of early treatment in this cohort lies in the absence of clear criteria to select patients who could be expected to benefit from early anti-TNF therapy. Kugathasan et al recently showed that early anti-TNF use is associated with less penetrating complications (HR 0.30, 95% CI 0.10 to 0.89; p=0.0296) but not less stricturing complications (HR 1.13, 95% CI 0.51 to 2.51; p=0.76) 22. These data suggest that early intervention may not be appropriate in all patients, even though we do not have clear predictors to discriminate the right patient for the right strategy.…”
Section: Introductionmentioning
confidence: 99%